1997
DOI: 10.1007/s003359900462
|View full text |Cite
|
Sign up to set email alerts
|

Towards interbreed IBD fine mapping of the mh locus: Double-muscling in the Asturiana de los Valles breed involves the same locus as in the Belgian Blue cattle breed

Abstract: The Spanish "Asturiana" cattle breed is characterized by the segregation of a genetically determined muscular hypertrophy referred to as double-muscling or "culones". We demonstrate by linkage analysis that this muscular hypertrophy involves the mh locus previously shown to cause double-muscling in the Belgian Blue cattle breed, pointing towards locus homogeneity of this trait across both breeds. Moreover, using a twopoint and multipoint maximum likelihood approach, we show that flanking microsatellite markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 11 publications
4
22
0
Order By: Relevance
“…Asturiana and Belgian Blue are known to carry the same variant at the GDF-8 locus, which is different from that found in Piedmontese (Dunner et al, 1997;McPherron and Lee, 1997;Grobet et al, 1998). The majority of the Belgian Blue and Asturiana samples were homozygous for an 11-bp deletion (mh) previously reported in these breeds (Belgian Blue: 96% mh/mh, 4% +/mh; Asturiana: 88% mh/mh, 10% +/mh, 2% +/+) (Dunner et al, 1997;Grobet et al, 1997). We did not know the frequency of the double-muscling mutation in the Piedmontese sample used, but the estimated frequency of double muscling for that population is close to 100%.…”
Section: Breed Samplesmentioning
confidence: 86%
“…Asturiana and Belgian Blue are known to carry the same variant at the GDF-8 locus, which is different from that found in Piedmontese (Dunner et al, 1997;McPherron and Lee, 1997;Grobet et al, 1998). The majority of the Belgian Blue and Asturiana samples were homozygous for an 11-bp deletion (mh) previously reported in these breeds (Belgian Blue: 96% mh/mh, 4% +/mh; Asturiana: 88% mh/mh, 10% +/mh, 2% +/+) (Dunner et al, 1997;Grobet et al, 1997). We did not know the frequency of the double-muscling mutation in the Piedmontese sample used, but the estimated frequency of double muscling for that population is close to 100%.…”
Section: Breed Samplesmentioning
confidence: 86%
“…As an important gene regulator of muscle growth and development, the MSTN gene has been well studied in livestock such as cattle (Dunner et al, 1997;Grobet et al, 1998;Casas et al, 1999) and pigs (Sonstegard et al, 1998;Li et al, 2002). However, the relationship between the MSTN gene variants and the meat produced as well as the meat quality in rabbits is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…The only base mutation lies in the upstream regulatory region, implying that MSTN gene expression and regulation vary in different species of livestock. For example, the cattle MSTN gene is located on the 2nd autosomal (Dunner et al, 1997), and some studies have found that the cattle double-muscle trait is caused by mutations in this gene. An SNP (G→A conversion) in the MSTN gene exon 3 of Piedmont cattle causes the tyrosine to replace cysteine (Grobet et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas LD has been extensively used in humans or mice, positional cloning experiments in domestic animals have seldom used this approach (Dunner et al 1997;Riquet et al 1999). This is rather paradoxical, as the population structure in domestic ruminants seems particularly adapted to LD analysis.…”
Section: Pis Linkage Disequilibrium Mappingmentioning
confidence: 94%